Anti-Depopulation Policy as a Method for Boosting Russia’s National Security - Vladimirovna Gnezdova, Julia; Iosifovich Deren, Vasiliy; Nikolaevna Rudakova, Elena; Vladimirovna Karapetyants, Irina; Anatolievna Safronova, Anastasia (International Journal of Engineering and Technology, 2018)
This paper makes a case for that declines in population size must be counteracted via a well-substantiated anti-depopulation policy. Russiaâ€™s current anti-depopulation policy has yet to live up to its potential. The linkage between depopulation and social/economic processes taking place across the Russian Federation may well be associated with the nationâ€™s rather inhomogeneous, polarized natural-terrain, territorial-economic, and settlement structure and marked differentiation in terms of major demographic and natural/economic determinants. By its subject matter, the issue of depopulation has long stopped being strictly scientific â€“ it now also has a political, economic, and ethnocultural ring to it. In this context, â€˜The Concept on Demographic Policy in the Russian Federation for the Period through to 2025â€™ expressly sets out the goals, principles, objectives, and key focus areas for Russiaâ€™s demographic policy, as well as the mechanisms for implementing it and curbing depopulation. However, all these postulates have thus far failed to be a factor for rational activity and greater responsibility for implementing set objectives on the part of relevant public authorities, which is affecting the nationâ€™s geopolitical security.Â Â Â